Pengaruh Ketebalan Mulsa Organik Ki Rinyuh (Chromolaena Odorata) Terhadap Kandungan Ndf, Adf, Dan Selulosa Rumput Gajah Mini (Pennisetum Purpureum Cv. Mott) - Minggo, Flavianus Perangko; Osa, Dominggus. B.; Temu, Stefanus T.; Nastiti, Herayanti P (Yayasan Sumber Daya Manusia Cerdas, 2024)
This study aims to determine how the thickness of kirinyuh organic mulch affects the amount of crude NDF, ADF, and cellulose of mini elephant (Pennisetum purpureum cv. Mott). Mini elephant grass (Pennisetum purpureum cv. Mott), and kirinyuh organic mulch (Chromolaena Odorata) were in this study. Randomized block design (RBD) were used in the study. There were four treatments with different thicknesses of mulch applied: M0 = control/without mulch, M1 = 1cm, M2 = 3cm, and M3 = 5cm) and four replications resulting in 16 experimental units. The variables studied were the content of NDF, ADF, and cellulose. Data were analyzed with Analysis of Variance (ANOVA) and Duncan's further test. The results of the analysis of variance (ANOVA) showed that the treatment had not significant effect (P>0.05) on the content of NDF and Seulosa but had a significant effect (P<0,05) on the content of ADF mini elephant grass (Pennisetum purpureum cv. Mott). Duncan's further test results showed that between treatments M0: M1 : M2 : M3 was significant different (P<0.05) and between treatments M1: M2: M3 was not significant different (P>0.05) on ADF content mini elephant grass (Pennisetum purpureum cv. Mott). In conclusion, the content of crude protein, crude fiber, and crude fat in mini elephant grass (Pennisetum purpureum cv) decrease in accordance with the kirinyuh organic mulch (Chromolaena odorata) was applied with varying thicknesses. The best M1 treatment had average NDF 69,75±0,98, ADF 33,75±2,76 and Cellulose 25,82±1,65